2016
DOI: 10.1007/s10237-016-0827-9
|View full text |Cite
|
Sign up to set email alerts
|

Computational modelling of local calcium ions release from calcium phosphate-based scaffolds

Abstract: A variety of natural or synthetic calcium phosphate (CaP)-based scaffolds are currently produced for dental and orthopaedic applications. These scaffolds have been shown to stimulate bone formation due to their biocompatibility, osteoconductivity and osteoinductivity. The release of the Ca 2+ ions from these scaffolds is of great interest in light of the aforementioned properties. It can depend on a number of biophysicochemical phenomena such as dissolution, diffusion and degradation, which in turn depend on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Nevertheless, quite often it is found that drug release is also controlled by the dissolution process of the dispersed drug particles in the matrices [ 9 , 10 ]. The effects of a finite dissolution rate have been observed for rather insoluble substances [ 11 , 12 ]. It is, therefore, necessary to develop a more general dissolution-diffusion model to describe release behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, quite often it is found that drug release is also controlled by the dissolution process of the dispersed drug particles in the matrices [ 9 , 10 ]. The effects of a finite dissolution rate have been observed for rather insoluble substances [ 11 , 12 ]. It is, therefore, necessary to develop a more general dissolution-diffusion model to describe release behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Using an interface-based method could enable the implementation of other surface-based processes, including the degradation and subsequent resorption of biodegradable implants as described by previous work of Manhas et al (2017). This would only require tracking an additional interface, whose propagation velocity (= resorption speed) might depend on the type of adjacent tissue and loading history.…”
Section: Discussionmentioning
confidence: 99%
“…Dissolution was represented using the Voxel-FEM approach. Additionally, a reaction-diffusion modeling approach was proposed for the simulation of degradation of calcium phosphate scaffolds [109]. Recently, a generic mathematical framework for the simulation and design of dissolution of biomaterials for tissue engineering and drug delivery applications has been introduced [110].…”
Section: Modeling Of Physical Phenomenamentioning
confidence: 99%